STRATEGI PEMASARAN BIMBINGAN BELAJAR DALAM MENGHADAPI PERSAINGAN DAN TANTANGAN DI ERA MODERN PADA BIMBEL AHE ANAK HEBAT KAJEN - Shinta Alvy Rizqiyana; Ana Aufa Hanifah; Isti Ghotsah; Masrurotul Usna; Ferida Rahmawati (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2025)
The era of globalization emerged as a result of advances in the way each individual thinks. Conditions in this global era make life increasingly competitive, so everyone is required to continuously improve their quality and abilities to stay ahead of the curve and be able to compete in tight competition. This research method uses a qualitative approach as part of the applied methodology. The results of this study explain that Bimbel Ahe Anak Hebat has succeeded in building a strong and efficient marketing foundation by integrating a simple digital approach and a social-personal approach in a community environment that is thick with family values. The main strengths of the implemented strategy are cost efficiency and social trust. However, Bimbel Ahe Anak Hebat still faces two main challenges as a pioneering tutoring center: limited reach and industry competition. Overall, the combination of strategies that focus on a personal approach and supported by simple digital media has been the key to Bimbel Ahe's success in building a positive image, although the challenges of expanding reach and improving professionalism still need to be overcome.